2020
DOI: 10.1186/s12910-020-00493-3
|View full text |Cite
|
Sign up to set email alerts
|

Moral competence, moral teamwork and moral action - the European Moral Case Deliberation Outcomes (Euro-MCD) Instrument 2.0 and its revision process

Abstract: Background: Clinical Ethics Support (CES) services are offered to support healthcare professionals in dealing with ethically difficult situations. Evaluation of CES is important to understand if it is indeed a supportive service in order to inform and improve future implementation of CES. Yet, methods to measure outcomes of CES are scarce. In 2014, the European Moral Case Deliberation Outcomes Instrument (Euro-MCD) was developed to measure outcomes of Moral Case Deliberation (MCD). To further validate the inst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 40 publications
(83 reference statements)
1
22
0
Order By: Relevance
“… 44 Goals, among others, are enhancing moral sensibility and responsiveness to the needs of patients and families. 45 However, the deliberation needs to be adapted to first depart from participants’ experiences of their own stress to be able to focus on the suffering of the patient and family. 46 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 44 Goals, among others, are enhancing moral sensibility and responsiveness to the needs of patients and families. 45 However, the deliberation needs to be adapted to first depart from participants’ experiences of their own stress to be able to focus on the suffering of the patient and family. 46 …”
Section: Discussionmentioning
confidence: 99%
“…Moral case deliberation is a facilitator-led collective moral inquiry by staff into a concrete moral issue connected to a real patient situation in their practice 44. Goals, among others, are enhancing moral sensibility and responsiveness to the needs of patients and families 45. However, the deliberation needs to be adapted to first depart from participants’ experiences of their own stress to be able to focus on the suffering of the patient and family 46…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of clinical ethics support CES evaluation (review) studies are increasingly focusing on quite different things; such as structure, process, content, outcomes and e ciency of CES [18][19][20][21][22][23][24][25][26][27][28][29] [2]. CES evaluation studies are of crucial importance since they may contribute to the further development of the relatively young professional domain of CES.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, high quality prospective CES evaluation studies which include baseline and follow-up measurements are rare [23,25,[40][41][42]. A recent Cochrane review, studying the available evidence of controlled studies of the effectiveness of ethical case interventions for adult patients, included 6 articles from 4 randomised trials, concluded that it was not possible to determine the effectiveness of CES due to low quality of the evidence presented in those studies [43].…”
Section: Introductionmentioning
confidence: 99%